2012
DOI: 10.5923/j.env.20120203.05
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Uptake, Growth and Phytochelatin Contents of <i>Triticum </i><i>A</i><i>estivum</i> in Response to Various Concentrations of Cadmium

Abstract: Cadmium (Cd) contamination of the environment is a major concern because of its impact on human health, food supply chain, and ecosystems. Phytoremediation has emerged as an alternative technology to expensive engineering techniques. The objectives of this research were to evaluate the growth and cadmium uptake of wheat (Triticum aestivum L. cv TAM 109) plants exposed to Cd at different periods; and assess whether phytochelatin (PC) synthesis can explain the wheat's tolerance mechanism to cadmium. Wheat seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Zhang et al [ 170 ] suggested that principal Cd detoxification mechanism in hyperaccumulator Sedum alfredii mediated by PCs occurs in shoots, which is similar to nonresistant plants. However, this event for wheat plant, as an efficient Cd accumulator, happened in roots [ 171 ]. In hyperaccumulators, it appears that they adopt mechanisms that involve long-distance translocation of PCs from root to shoot [ 172 ].…”
Section: Some Defense Mechanisms Employed By Plants Against Hm Strmentioning
confidence: 99%
“…Zhang et al [ 170 ] suggested that principal Cd detoxification mechanism in hyperaccumulator Sedum alfredii mediated by PCs occurs in shoots, which is similar to nonresistant plants. However, this event for wheat plant, as an efficient Cd accumulator, happened in roots [ 171 ]. In hyperaccumulators, it appears that they adopt mechanisms that involve long-distance translocation of PCs from root to shoot [ 172 ].…”
Section: Some Defense Mechanisms Employed By Plants Against Hm Strmentioning
confidence: 99%
“…The translocation of Cd from root to shoot is through the xylem appears to be the main process for shoot accumulation. At a relatively high Cd treatment (20 μM) phytochelatin biosynthesis was enhanced more evidently in shoots [50]. The phytochelatin independent mechanism of tolerance of higher plants to Cd toxicity also exists and can be attributed to the highly developed apoplastic transport systems [51].…”
Section: Phytochelatins (Pcs) As Heavy Metal Chelatorsmentioning
confidence: 99%